„Honour him for ever!” Reports of the death and funeral of the master and patriot Jan Matejko (1838–1893) - Glugla, Paweł (Requiem, 2025)
Jan Matejko, is the most famous and respected figure on the artistic-painting-patriotic plane in Poland of the 19th century. Called “Master” by his students, he served Krakow, as well as the whole of Poland and all his compatriots, well. His works were admired and awarded both at home and far beyond its borders. He was an informal ambassador for the Poles and for Poland, which at that time did not exist politically on the maps of Europe. He passed on his extraordinary talent and secrets of the difficult art of painting with passion and great commitment to young, talented students. He organised an independent School of Fine Arts in Krakow in 1873 and directed it until his premature death on 1 November 1893. A ceremonial funeral for Matejko took place on 7 November 1893, which was a tribute to the memory of the artist, master and friend, as well as a great patriotic manifestation. The master was remembered by both the mighty and the poor, whom he supported daily. He was a well-known and highly regarded painter in Poland and throughout the world. His untimely death and funeral echoed loudly not only in the Polish lands, but far beyond.